2020
DOI: 10.1093/cvr/cvaa034
|View full text |Cite
|
Sign up to set email alerts
|

RUNX1: an emerging therapeutic target for cardiovascular disease

Abstract: Runt-related transcription factor-1 (RUNX1), also known as acute myeloid leukaemia 1 protein (AML1), is a member of the core-binding factor family of transcription factors which modulate cell proliferation, differentiation, and survival in multiple systems. It is a master-regulator transcription factor, which has been implicated in diverse signalling pathways and cellular mechanisms during normal development and disease. RUNX1 is best characterized for its indispensable role for definitive haematopoiesis and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 186 publications
(242 reference statements)
4
54
0
Order By: Relevance
“…14j). The role of RUNX1 has been primarily studied in cardiomyocytes 41 where deficiency protects against ischemic injury 42 . In the heart, the role of RUNX1 in non-myocytes is not defined in detail yet one recent study has reported the RUNX1 binding motif as a main motif in cardiac fibroblast-specific active enhancers 43 .…”
Section: The Direction Of the Trajectory Was Further Confirmed By An mentioning
confidence: 99%
“…14j). The role of RUNX1 has been primarily studied in cardiomyocytes 41 where deficiency protects against ischemic injury 42 . In the heart, the role of RUNX1 in non-myocytes is not defined in detail yet one recent study has reported the RUNX1 binding motif as a main motif in cardiac fibroblast-specific active enhancers 43 .…”
Section: The Direction Of the Trajectory Was Further Confirmed By An mentioning
confidence: 99%
“…Runx1 also regulates the development and transcription during hematopoiesis [ 19 – 21 ]. Recently, Runx1 was demonstrated to be involved in the processes underlying adverse cardiac remodeling [ 22 ], and Runx1 activation in cardiomyocytes after MI is harmful to ventricular function [ 23 ]. However, to date, the protective role of Runx1 against adverse cardiac remodeling after MI in response to dihydrolycorine treatment remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…RUNX1 upregulation is related to impaired cardiac contractile function and cardiac remodeling ( McCarroll et al, 2018 ). Runx1 knock-out can protect against adverse cardiac remodeling after AMI in mice ( Riddell et al, 2020 ). Moreover, Runx1 mRNA expression increases in the blood of AMI patients ( Mao et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%